Urgency of The Essential Medicine Definition's Regulation in Indonesian Law System: URGENSI PENGATURAN DEFINISI OBAT ESENSIAL DALAM REGULASI HUKUM DI INDONESIA - Setiawan, Bagus Catur; sulistyowati, eny (Universitas Negeri Surabaya, 2022)
Abstract Health problems are one of the life factors that reflect the fulfillment of basic human needs. The Indonesian government has issued regulations to tackle health problems, but in practice there are still many uses of the term drug in regulations, which causes confusion, one of which is the definition of essential medicine. Definition of Drugs Found in Presidential Regulation Number 94 of 2007 but in the Health Law the term essential medicine does not exist. In this case the researcher recommends that the regulation should include the term essential medicine. This type of legal research is included in normative legal research. The approach used in this research is the conceptual approach (Conceptual Approach) and statute approach (Statute Approach. The legal materials used are Presidential Regulation Number 94 of 2007 concerning Control and Supervision of the Procurement and Distribution of Drug Materials, Specific Medicines and Medical Devices, Law Number 36 of 2009 concerning Health .Based on the results of research conducted by researchers, the importance of defining essential drugs is an important element in health management so that the stakeholders who are punished in this case need to form a definition of Essential Medicines in Law Number 36 of 2009 with NLEM regulations and Presidential Regulation Number 94 of 2007 concerning Control and Supervision of the Procurement and Distribution of Medicinal Substances, Specific Drugs and Medical Devices that Function as Drugs. This is a form of legal certainty for the community and stakeholders. Keywoards : Health,Essential medicines,National essential medicines list